The Influence of Instagram Account Content @Jktinfo on Information Needs - Rosiana, Rosa; Pramono Hadi, Sigit (Zona Education Indonesia, 2024)
Many people cannot avoid technological developments which will continue to develop over time. Information and communication technology has made it easier and faster for people and cultures to interact with each other. Because many people still use technology to do their work, this cannot be separated. With the internet, technology makes it easier to spread and expand information. Ease of accessing the internet can be used anywhere and can be used on a PC, cellphone or tablet. Currently, social media is not only used to convey information but can also be used to search for information. The phenomenon that is currently happening is that many Instagram social media provide information about a particular area, such as the @jktinfo account, the content provided is such as providing information in the form of pictures and videos regarding news in Jakarta. The aim of this research is to find out whether the content of the Instagram account @jktinfo influences the information needs of STIKOM Interstudi students class of 2019. This research uses the uses and gratifications theory. The method used is an explanatory survey using a quantitative approach. Sample testing was carried out using a non-probability sampling technique with purposive sampling type. The results of this research show that the @jktinfo Instagram Account Content on Information Needs has a moderate level of positive influence with a percentage of 44.9%, while 55.1% is influenced by other variables not studied